Mesenchymal stem cells and their secreted molecules predominantly ameliorate fulminant hepatic failure and chronic liver fibrosis in mice respectively. Issue 1 (December 2016) - Huang, Biao; Cheng, Xixi; Wang, Huafeng; Huang, Wenjing; Ga hu, Zha; Wang, Dan; Zhang, Kai; Zhang, Huan; Xue, Zhenyi; Da, Yurong; Zhang, Ning; Hu, Yongcheng; et al.
Abstract Background Orthotopic liver transplantation is the only effective treatment for liver failure but limited with shortage of available donor organs. Recent studies show promising results of mesenchymal stem cells (MSCs)-based therapies. Methods We systematically investigate the therapeutic effects of MSCs or MSC-conditioned medium (MSC-CM) in ameliorating fulminant hepatic failure (FHF) and chronic liver fibrosis in mice. In addition, extensive flow cytometry analysis of spleens from vehicle and MSC- and MSC-CM-treated mice was applied to reveal the alteration of inflammatory state. Results In FHF model, MSCs treatment reduced remarkably the death incidents; the analysis of gross histopathology showed that control livers were soft and shrunken with extensive extravasated blood, which was gradually reduced at later time points, while MSC–treated livers showed gross pathological changes, even 24 h after MSC infusion, and hematoxylin and eosin staining revealed dramatical hepatocellular death with cytoplasmic vacuolization suppressed by MSCs treatment; flow cytometry analysis of total lymphocytes showed that macrophages (F4/80) infiltrated into control livers more than MSC-treated livers; by contrast, MSC-CM partially ameliorates FHF. In chronic liver injury model, MSC and MSC-CM both suppressed fibrogenesis and necroinflammatory, and the later was better; activation of hepatic stellate cells (α-SMA) was inhibited; glycogen synthesis and storage (indicated by periodic acid-Schiff -staining) was improved; liver regeneration (Ki67) was promoted while liver apoptosis (TUNEL) was reduced. In the in vitro, MSCs promote macrophage line RAW264.7 apoptosis and MSC-CM promotes apoptosis and inhibits proliferation of HSC line LX-2. We also found that MSCs and MSC-CM could improve spleen; MSC-CM increased levels of Th2 and Treg cells, and reduced levels of Th17 cells, whereas levels of Th1 cells were unchanged; comparatively, MSC treatment did not affect Th17 and Treg cells and only slightly alters inflammatory state; MSC and MSC-CM treatment both substantially down-regulated macrophages in the spleens. Conclusion Both MSCs and MSC-CM exert therapeutic effects by acting on various key cells during the pathogenesis of FHF and chronic fibrosis, stimulating hepatocyte proliferation and suppressing apoptosis, down-regulating infiltrating macrophages, converting CD4+ T lymphocyte system into an anti-inflammatory state, and facilitating hepatic stellate cell death.